2006
DOI: 10.1007/s00268-005-0749-7
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Serous Oligocystic Adenomas: Clinicopathologic Features and a Comparison with Serous Microcystic Adenomas and Mucinous Cystic Neoplasms

Abstract: SOAs and SMAs have similar clinicopathologic features. On the other hand, SOAs differ from MCNs by their relatively higher male/female ratio, higher frequency of tumors occurring in the head of the pancreas, and smaller cyst size. Knowledge of these distinguishing clinical features when used in combination with other diagnostic modalities such as endoscopic ultrasonography/fine-needle aspiration will enable clinicians to better differentiate these two pathologic entities preoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 39 publications
2
53
0
3
Order By: Relevance
“…A pre-operative distinction between SOA and MCN is of the utmost importance because MCN is considered to be potentially malignant and should be surgically resected [8]. Because SOA cystic spaces are larger than those of serous microcystic adenoma, they can be mistaken for MCN on imaging.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A pre-operative distinction between SOA and MCN is of the utmost importance because MCN is considered to be potentially malignant and should be surgically resected [8]. Because SOA cystic spaces are larger than those of serous microcystic adenoma, they can be mistaken for MCN on imaging.…”
Section: Resultsmentioning
confidence: 99%
“…Because the cystic spaces are .2 cm, SOA images can be mistaken for mucinous cystic neoplasm (MCN), pseudocyst or intraductal papillary mucinous tumour [2,[5][6][7]. It is very difficult to differentiate SOA from MCN by clinical and radiological features [2,6,8,9]. SOA does not require resection unless it causes symptoms, but MCN should be resected because of a potential for malignant degeneration [5,7,8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy of CT in diagnosis of SCA in comparison to other cystic neoplasms has been reported in several previous studies which found accuracy ranging from 27%-93% [17][18][19] . More recent studies have compared SOAs with MCNs and IPMNs and have emphasized the importance of patient demographics, lesion location and shape of the cyst in characterization of the various lesions [4,10,15] . However, our study is unique as we have assessed the predictive value of specific features of SCA on MDCT in a large cohort of patients with surgically verified pancreatic cystic lesions and have evaluated how well the CT features correlate with pathology.…”
Section: Mdct Features Pathology Findingsmentioning
confidence: 99%
“…While SCAs are relatively uncommon in comparison to pseudocysts and solid tumors of the pancreas, their clinical importance is indisputable. Though generally regarded as benign, 3% of SCAs have malignant potential with local infiltration and distant metastases [1,[3][4][5] . These are slow growing tumors; however the growth rate varies depending on tumor size.…”
Section: Introductionmentioning
confidence: 99%